A cellular antidote to specifically deplete anti-CD19 chimeric antigen receptor–positive cells - Ruella, Marco (Blood, 2020)
Unintentional transduction of B-cell acute lymphoblastic leukemia blasts during CART19 manufacturing can lead to CAR19(+) leukemic cells (CARB19) that are resistant to CART19 killing. We developed an anti-CAR19 idiotype chimeric antigen receptor (αCAR19) to specifically recognize CAR19(+) cells. αCAR19 CAR T cells efficiently lysed CARB19 cells in vitro and in a primary leukemia-derived xenograft model. We further showed that αCAR19-CART cells could be used as an “antidote” to deplete CART19 cells to reduce long-term side effects, such as B-cell aplasia.